Introduced greenhouse-invertebrates in Potsdam and Berlin with a focus on ants (Hymenoptera, Formicidae) with eight new records for Europe, Germany or the Berlin-Brandenburg region - Elias Freyhof; Emil Janke (Contributions to Entomology)
Heated greenhouses are a hotspot for introduced species from warmer climates. We studied 24 greenhouses for their invertebrate fauna with a special focus on ants. Identifications were initialised by iNaturalist and its community, followed by literature, COI barcoding and consulting experts in some cases. We report 32 introduced species including eight new records at the regional, national or continental scale, four of which are ants. Technomyrmex difficilis and Solenopsis texana are recorded for the first time in Germany. Plagiolepis alluaudi and Technomyrmex vitiensis are new for Berlin and Brandenburg. Alepia cf. viatrix (Diptera, Psychodidae) is first recorded for continental Eurasia. Cryptotermes cavifrons (Blattodea, Kalotermitidae) and Geonemertes pelaensis (Hoplonemertea, Prosorhochmidae) are recorded the first time for Europe. An unidentified species of the genus Anisorhynchodemus (Tricladida, Geoplanidae) is recorded the first time for Germany. Here, we present records for 37 species (five of the ant species are native), all associated with pictures in iNaturalist. For 33 individuals of 20 species, we also provide COI sequence data supporting their identification. Furthermore, the comparison of greenhouse metadata with species composition showed that the introduced ant species are dependent on a high minimum temperature in the greenhouse.